The Effect of Arabic Infinitives on Persian Word Formation: An Application of Johnson’s “Lexical Variation Theory” Using a statistical model (based on the story Dar Ol-Majanin; Malakoot and Gileh Mard - Farzaneh Haji Qasemi; Somayeh Kazemi NajafAbadi (ادبیات تطبیقی, 2019)
Along with human relationships, languages are in continuous exchange. The clearest evidence for language exchange is the existence of loan words in a language. Considering the long history of Iran-Arab relations, Persian has borrowed some of its words from Arabic. It is a matter of high importance to investigate and recognize these words in Persian morphology. Thus, the present paper tries to explore Arabic infinitives used in the structure of Persian words in three leading literary works of Iranian fiction writing, namely, Dar al-Majanin by Mohammadali Jamalzadeh, Malakoot by Bahram Sadeqiand Gileh Mard by Bozorg Alavi, using a descriptive- analytical method and statistic data, and based on Johnson’s lexical variation theory. The findings of this statistical research suggest that thulathi mujarrad Arabic infinitives have been used extensively in the structure of contemporary Persian words during the last 40 years. However, this has been a descending trend.